EKSTENSIVITAS OBJEK SENGKETA TATA USAHA NEGARA MENURUT UNDANG-UNDANG NOMOR 30 TAHUN 2014 TENTANG ADMINISTRASI PEMERINTAHAN - Suanro (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2016)
The formulation of Article 87 of Law Number 30 Year 2014 on Government Administration, lead to the expansion of the object of dispute that can be tested in the courts of the state administration. It is caused by a state administrative decision meaning as defined in the legislation administrative courts have expanded meaning. According to the law state administrative court, the factual action of officials does not include dispute object of state administration. While the law of public administration to formulate the decision of the state administration is a written determination that includes factual action. The formulation add absolute competence of administrative courts which originally was not authorized to examine the factual actions of government officials who violate the law. Benchmarks in determining the competence of administrative courts under the laws of the government administration uses benchmarks the subject of the dispute, the parties dispute that is the subject of state administration.